Итоги кольцевания рукокрылых в Украинской ССР за 1939—1967 гг. Сообщение III - Абеленцев, В.И.; Колюшев, И.И.; Крочко, Ю.И.; Татаринов, К.А. (Вестник зоологии, 1970)
The communication deals with 1224 individuals of Chiroptera (6 species) out of 3875 (14 species) marked in the Ukraine. 150 animals (out of 1224) are met repeatedly Nyctalus leisleri—11, Nyctalus noctula — 119, Pipisterllus pipistrellus—18, P.pipistrellus Natuzius—1, Eptesicus serotinus—1. Besides, 7 Nyctalus noctula are found, ringed beyond the boundaries of the republic (animals, ringed in the Voronezh reservation, are met repeatedly in Zaporozhie, Crimea, Kirovograd, Rovno, Khmelnitsky and Ivano-Frankovsk regions). P.pipistrellus, ringed in the Dnepropetrovsk region, was met in the South Bulgaria. He flew 1150 km.
The data are presented on maximum distances, at which Chiroptera can fly, on terms of ring carrying and also the information on the population ecology is given.